Launched during the Pandemic, How @teman_bus Promote Cashless-Based Public Transportation. - Zhafira, Gazi; Ismi Dwi Astuti Nurhaeni; Ignatius Agung Satyawan (Lafadz Jaya Publisher, 2024)
Teman Bus is an implementation of the Buy The Service program from the Ministry of Transportation Indonesia which was launched in 11 Indonesian cities during the pandemic and requires cashless system. This study raises the question of transitioning from a free subsidy system to a paid cashless system in public transportation by 2023. What kind of promotional strategy has Teman Bus employed to capture the public's attention to adaptation? Using content analysis with a qualitative approach, through the Instagram of @teman_bus, researchers aim to examine the promotional strategies employed in the content uploads by Teman Bus. The resulting findings are that @teman_bus takes advantage of renewal along with adapting to new pandemic habits, following a great content strategy which consists of credibility, shareable, useful or fun, interesting, relevant, different and on brand such as centralized content from ministry of transportation, regularly holding giveaways and the most prominent approach is its 'on brand' consistency using repetition and persistence for uploading the content, the repetitive nature of the predetermined content template serves as a persistent promotional strategy, effectively garnering attention, facilitating learning, and promoting a shift in people's habits towards using cashless methods with Teman Bus for public transportation.